Exploring the potential of fungal arylacetonitrilases in mandelic acid synthesis - Veselá, Alicja B; Křenková, Alena; Martínková, Ludmila (Molecular biotechnology, 2015)
The application of arylacetonitrilases from filamentous fungi to the hydrolysis of high concentrations of (R,S)-mandelonitrile (100-500 mM) was demonstrated for the first time. Escherichia coli strains expressing the corresponding genes were used as whole-cell catalysts. Nitrilases from Aspergillus niger, Neurospora crassa, Nectria haematococca, and Arthroderma benhamiae (enzymes NitAn, NitNc, NitNh, and NitAb, respectively) exhibited different degrees of enantio- and chemoselectivity (amide formation). Their enantio- and chemoselectivity was increased by increasing pH (from 8 to 9-10) and adding 4-10% (v/v) toluene as the cosolvent. NitAn and NitNc were able to convert an up to 500 mM substrate in batch mode. NitAn formed a very low amount of the by-product, amide (<1% of the total product). This enzyme produced up to >70 g/L of (R)-mandelic acid (e.e. 94.5-95.6%) in batch or fed-batch mode. Its volumetric productivities were the highest in batch mode [571 ± 32 g/(L d)] and its catalyst productivities in fed-batch mode (39.9 ± 2.5 g/g of dcw). NitAb hydrolyzed both enantiomers of 100 mM (R,S)-mandelonitrile at pH 5.0 and is therefore promising for the enantioretentive transformation of (S)-mandelonitrile. Sequence analysis suggested that fungal arylacetonitrilases with similar properties (enantioselectivity, chemoselectivity) were clustered together.
Keywords: Species Specificity; Nectria; kyseliny mandlové; fylogeneze; Aminohydrolases; Hydrogen-Ion Concentration; aminohydrolasy; koncentrace vodíkových iontů; druhová specificita; Arthrodermataceae; Fungal Proteins; Mandelic Acids; fungální proteiny; Phylogeny; Neurospora crassa; Aspergillus niger